Dystrophic epidermolysis bullosa in a child - Uma Eswara (Wolters Kluwer Medknow Publications, 2012)
Epidermolysis Bullosa (EB) is a form of severe skin adhesion defect due to the disruption of the dermal- epidermal junction. It is classified into simplex and dystrophic forms depending on the level at which the junction is compromised. Repeated ulcerations and bullae formation in the mouth lead to scarring that brings about various changes in the oral cavity. These include loss of sulcular depth, ankyloglossia, limited mouth opening and other dentoalveolar changes. At present while there is no cure for EB, the therapeutic approaches are essentially aimed at controlling the infections and maintaining an acceptable quality of life. Dental management should aim at maintaining a functional dentition that would help in mastication and favour nutrition. Oral manifestations and dental management in a child diagnosed with dystrophic EB since birth are presented here.